Knowledge, attitude, and practice of aesthetic medicine practitioners towards laser and/or light therapy for hypertrophic scars - Wenhui Yang; Lei Yang; Huizheng Li; Xingjian Cheng (Scientific Reports)
Abstract This study investigated the knowledge, attitude, and practice (KAP) of aesthetic medicine practitioners concerning laser and/or light therapy for hypertrophic scars. Conducted at Hebei Medical University Third Hospital from December 25, 2023, to January 7, 2024, the cross-sectional study utilized a self-administered questionnaire to gather socio-demographic data and KAP scores. A total of 424 valid questionnaires were collected, with 220 (52.26%) female participants. The mean scores were 27.24 ± 4.28 for knowledge (range 8–40), 34.14 ± 3.49 for attitude (range 9–45), and 26.22 ± 3.46 for practice (range 6–30). Significant positive correlations were observed between knowledge and attitude (r = 0.471, P < 0.001), knowledge and practice (r = 0.593, P < 0.001), and attitude and practice (r = 0.640, P < 0.001). Multivariate logistic regression revealed that both knowledge (OR = 1.260, P < 0.001) and attitude scores (OR = 1.547, P < 0.001), along with the intermediate professional title (OR = 0.233, P = 0.042), were significantly associated with proactive practice. The findings indicate a need for targeted educational initiatives to enhance practitioners’ knowledge in this area.